Preliminary Study of Accounting Application at The Micro Small and Medium Enterprises (MSMEs) in Bandar Lampung - Rusmianto Rusmianto (Politeknik Negeri Lampung, 2011)
This study wanted to know how the application of accounting at the micro small and medium enterprises (MSMEs), especially MSMEs in the town of Bandar Lampung as a first step in establishing research and development activities are appropriate at a time when that will come. The variables that will be seen as the application of accounting in MSMEs are: recording system and reporting for financial transactions, knowledge of micro small and medium businesses (MSMEs) on accounting, knowledge of micro small and medium businesses (MSMEs) about the tax, the use of information technology in business, and business decision-making system. The conclusion that can be generated from research that uses 55 micro small medium enterprises (MSMEs) as a sample of the research are: the micro small and medium businesses (MSMEs), most have not been doing the accounting process as a recording system that produces financial reports.Â The small micro business medium enterprises (MSMEs) have sufficient knowledge about the concept - general concepts of accounting but does not have sufficient knowledge about accounting process itself.Â Most of the small and medium businesses (MSMEs) do not have enough knowledge about taxation. the majority of the perpetrators of small and medium enterprises (MSMEs) are not applying information technology in their business field. Most of the small and medium businesses (MSMEs) make operational decisions with a rational business but still make plans only limited in memory just is not translated in the form of documents. Â Keywords: Accounting Aplication, Micro Small and Medium Enterprises